Evolution of Aminoglycoside Resistance in CTX-M-15 Producing Klebsiella Spp. in Kurdistan Province, Iran - Pegah Shakib (Journal of Research in Medical and Dental Science, 2018)
The aim of present investigation was evolution of aminoglycoside resistance in CTX-M-15 producing klebsiella spp. Clinical isolates from general hospitals of Kurdistan Province, Iran. Ninety klebsiella spp. isolates were obtained from different clinical specimens. Antibiotic susceptibility pattern and detection of ESBL producing isolates performed by Kirby-Bauer disc diffusion method according to Clinical and Laboratory Standards Institute’s (CLSI) guidelines. CTX-M-15 gene screened by PCR amplification. Fisher tests was used to analyses by with STATA software program and p-values below 0.05 were considered as significant. Out of 90 clinical isolates the highest and lowest resistance related to cefotaxime and imipenem respectively. The results of detection of ESBL producing isolates showed that 62 isolates (84.4%) were ESBL-positive isolates. Thirty two (42.1%) out of 90 Klebsiella spp. isolates caring CTX-M-15 gene. CTX-M-15 was detected in 56.2% of gentamycin resistance, 34.4% of kanamycin resistance, and 56.2% of amikacin resistance. the present study showed that there was high frequency of CTX-M-15 gene in ESBL producing clinical isolates in Kurdistan Province, Iran. Moreover, there was no statistically significant relationship between CTX-M-15 production and resistance to aminoglycoside antibiotics in Klebsiella spp. isolates.